Tailoring the optical properties of poly(diallyl dimethyl ammonium chloride) polyelectrolyte by incorporation of 2-mercaptoethanol capped CdSe nanoparticles. (9th September 2016) - Tyagi, Chetna; Sharma, Ambika
Abstract: The present work deals with the preparation and characterization of 2-mercaptoethanol capped cadmium selenide (CdSe) nanoparticles, dispersed in poly(diallyl dimethyl ammonium chloride) (PDADMAC) polyelectrolyte aqueous solution. X-ray diffraction spectra, scanning electron microscopy and energy-dispersive x-ray have been used to determine the structure, particle size ( d ), surface morphology and composition of various constituents. The absorption spectra of pure PDADMAC and the CdSe/PDADMAC polymer nanocomposite (PNC) are analyzed to determine the values of the absorption coefficient ( α ) and energy band gap ( E g ) which are found to be 4 eV and 3.26 eV respectively. A red shift in the spectrum of the PNC, as compared to the pure polymer, has been observed. With the addition of CdSe nanoparticles in the PDADMAC polyelectrolyte, a remarkable change in the optical parameters of the pure polymer has been observed. The refractive index ( n ) obtained by using Swanepoel's method decreases in the case of the PNC as compared to the pure polymer. The value of the static refractive index ( n 0 ) is found to be 4.29 for the pure polymer and 1.52 for the PNC. The extinction coefficient, dielectric constants, optical conductivity and relaxation time have been evaluated. The Wemple–DiDomenico model has been used to evaluate the dispersion parameters such as the average energy gap ( E 0 ) and dispersion energy ( E d ). The values of the nonlinear refractive index ( n 2 ) of the pure polymer and PNC have been determined using the theoretical approaches suggested by Boling and Tichy and Ticha. n 2 increases in the case of PNC, which relates to the decreased energy band gap. Photoluminescence (PL) spectra have been studied to explore the energy band structure and interaction between CdSe nanoparticles and PDADMAC. The PL peaks obtained at 437 nm and 461 nm correspond to the pure polymer whereas the peak at 577 nm is attributed to CdSe.